Pemberdayaan Petani Desa Lambadeuk melalui Sistem Intercropping Cabai–Nilam pada Lahan Marginal - Mujiburrahmad Mujiburrahmad; Agussabti Agussabti; Elly Kesumawati; Elviani Elviani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service activity aims to increase the productivity of marginal land and improve farmer capacity through the application of environmentally friendly agricultural technologies in Lambadeuk Village, Peukan Bada District, Aceh Besar Regency. The methods used included outreach, training, and mentoring based on learning by doing, with a focus on the use of mycorrhizae, the production of liquid organic fertilizer (POC), and the implementation of a chili–patchouli intercropping system based on Good Agricultural Practices (GAP). The results showed measurable improvements in farmer knowledge and skills, with average participant understanding increasing from 41% before training to 82% after, while practical skills increased from 30% to 78%. This activity also produced an initial batch of approximately 120 liters of POC applied to a demonstration plot, and successfully activated approximately 2.3 hectares of previously unproductive land for organic horticultural cultivation. The impact extended beyond individual farmer capacity to the economic and sustainability aspects of farming, including the emergence of independent fertilizer production initiatives and the establishment of simple local-level marketing systems. These activities made a measurable contribution to increasing land productivity, reducing production costs, and strengthening farmer independence in managing agricultural resources sustainably.